Market valuation of joint ventures: Joint venture characteristics and wealth gains - Park, Seung Ho; Kim, Dongcheol (Journal of Business Venturing, 1997)
Along with R&D and capital investment, interfirm linkages like joint ventures have been widely used by American corporations as an investment tool to enhance their entrepreneurial capabilities and long-run competitiveness. Today, it has become a common belief that cooperative strategy is the new form of competition facing the recent development in the world economy, technology, and corporate strategy. Companies use interfirm coordination to acquire new technologies and expand their product/market reach, which is the crux of corporate entrepreneurship. Interfirm linkages expand information and resource access by widening the sweep of environmental scanning for a firm and by linking with complementary assets in other corporations. And corporate entrepreneurialism through the pursuit of innovative capabilities or administrative structures is at the nexus of joint venturing among domestic or cross-border partners. Studies have consistently shown that the payoff of corporate entrepreneurship like joint ventures is long-term in nature. However, it is well known that for American managers, the biggest obstacle to long-run or entrepreneurial decision-making is the stock market. The business press and writers have claimed that the stock market forces managers to take a short-run view in their decision-making and deters corporate entrepreneurship. However, this claim is still not solidly grounded in empirical findings. The present study attempted to provide such evidence by examining wealth gains, i.e., stock market valuation, from corporate entrepreneurship of joint venturing between independent companies. Investors have an incentive to gather information and judge whether entrepreneurial decisions are good or bad in maximizing efficiency of the firm. The firm's stock price then reflects the market judgment of the likely payoffs from entrepreneurial activities even though these may be occurring in the long term. Previous studies have assumed that joint ventures have same financial implications as mergers and acquisitions, leading to abnormal returns at the announcement of such investment decisions. The current study revisits the conclusion on positive abnormal returns by focusing on various venture- and partner-specific contingencies that may affect performance of joint ventures. We theorize that shareholders perceive joint ventures differently according to the ventures' economic potential and the disposition of corporate governance. In particular, this study explores the cross-sectional difference in wealth gains, i.e., abnormal returns, at the announcement of joint ventures by relating the gains with various strategic and managerial contingencies; that is, the nature of relationship between partners, the relatedness and the strategic implication of joint ventures to partners, the extent of partners' control over joint ventures, and the corporate governance in parent firms. The data set consists of two-party equity joint ventures in the electronics industry that were launched between 1979 and 1988. The unit of analysis is the 174 U.S. firms out of 158 joint ventures, of which 113 were cross-border agreements and 45 were between U.S. firms. The study applies the event study method to assess stockholders' risk-adjusted wealth gains and a cross-sectional analysis based on a generalized least-squares model to test the hypotheses. Contrary to popular belief, our results show an overall favorable reaction to joint venturing in the stock market, even though there is substantial variation according to contextual influences. The findings show that stock market valuations reflect the economic potential of joint ventures and are affected by the degree and type of control shareholders and partners can exercise. The first key finding in the study is that the valuation effect of joint ventures is multifaceted; the market valuation of joint ventures depends on the relationship between partners, the nature of partners' contributions, the extent of partners' control over joint ventures, and the corporate governance in parent firms. Our findings also show that partner size, which has not been studied in prior studies, is a critical variable affecting wealth gains from joint ventures. Our results certainly shed light on understanding the effect of size on corporate wealth gains from joint ventures. The results provide conflicting support for most hypotheses depending on firm size, implying that joint ventures have different strategic and managerial implications for the partners depending on size. Shareholders tend to perceive joint ventures as a risky entrepreneurial operation particularly for the smaller partners. It is indeed difficult to protect the smaller partners' firm-specific know-how from being appropriated by the other partners. Accordingly, smaller firms' role and degree of control in a joint venture substantially affect wealth gains from their joint venturing with larger corporations. Shareholders value majority equity sharing by smaller partners as an important governance mechanism to control resource flows and avoid opportunistic behaviors by the larger partners. Whereas this study extends the previous findings on positive wealth gains of joint ventures by examining contextual influences, it also attempts to fill the void in the field of corporate entrepreneurship. Despite the growing interest in corporate entrepreneurship, there has been little attempt to empirically examine its potential association with corporate financial performance, in particular with market-based performance measures or wealth gains. Financial theory posits that accounting-based performance measures do not properly measure the value of managers' entrepreneurial decisions. Rappaport (1986) argued that the true measure of the long-run value of an investment decision is economic value for shareholders as measured by abnormal stock returns, i.e., wealth gains. Our study is an extension of this fast emerging field of study on the relationship between corporate entrepreneurship and financial performance by focusing on corporate wealth gains from joint venturing with other firms in pursuit of entrepreneurial goals.